Status of Developmental Readiness of Rural and Urban School Children - Joshi, Neha; Vig, Deepika (THE PRIMARY TEACHER, 2017)
This study aims to assess the status of developmental readiness of 200 students (100 boys and 100 girls) enrolled in Class I of private schools in rural and urban areas of Ludhiana district in Punjab. It also tries to find out locale difference in the developmental readiness of the students. The sample was selected through the random sampling method and the data were collected using self-structured developmental readiness checklist. Locale differences revealed that rural boys and girls showed significantly better socio-emotional skills and overall readiness than those living in urban areas.